Evolutionary origin and functional divergence of totipotent cell homeobox genes in eutherian mammals. Issue 1 (December 2016) - Maeso, Ignacio; Dunwell, Thomas; Wyatt, Chris; Marlétaz, Ferdinand; Vető, Borbála; Bernal, Juan; Quah, Shan; Irimia, Manuel; Holland, Peter
Abstract Background A central goal of evolutionary biology is to link genomic change to phenotypic evolution. The origin of new transcription factors is a special case of genomic evolution since it brings opportunities for novel regulatory interactions and potentially the emergence of new biological properties. Results We demonstrate that a group of four homeobox gene families (Argfx, Leutx, Dprx, Tprx ), plus a gene newly described here (Pargfx ), arose by tandem gene duplication from the retinal-expressedCrx gene, followed by asymmetric sequence evolution. We show these genes arose as part of repeated gene gain and loss events on a dynamic chromosomal region in the stem lineage of placental mammals, on the forerunner of human chromosome 19. The human orthologues of these genes are expressed specifically in early embryo totipotent cells, peaking from 8-cell to morula, prior to cell fate restrictions; cow orthologues have similar expression. To examine biological roles, we used ectopic gene expression in cultured human cells followed by high-throughput RNA-seq and uncovered extensive transcriptional remodelling driven by three of the genes. Comparison to transcriptional profiles of early human embryos suggest roles in activating and repressing a set of developmentally-important genes that spike at 8-cell to morula, rather than a general role in genome activation. Conclusions We conclude that a dynamic chromosome region spawned a set of evolutionarily new homeobox genes, the ETCHbox genes, specifically in eutherian mammals. After these genes diverged from the parentalCrx gene, we argue they were recruited for roles in the preimplantation embryo including activation of genes at the 8-cell stage and repression after morula. We propose these new homeobox gene roles permitted fine-tuning of cell fate decisions necessary for specification and function of embryonic and extra-embryonic tissues utilised in mammalian development and pregnancy.